Análisis del impacto económico de control predictivo basado en modelo económico en fotobiorreactores (2019)
In this thesis it was proposed a formulation to evaluate the economic impact of the use of Economic Model Predictive Control (EMPC). For this, a model of a photobioreactor (PBR) was proposed by combining different phenomena within the reactor for the cultivation of microalgae such as: fluid dynamics, photosynthesis kinetics and mass balances. The proposed model has a new characteristic, it is the inclusion of an empirical equation which takes into account the performance of the Light - Dark cycles in a dynamic mathematical model for the predictions of productivity in the PBR. Besides of that, an economic optimization was proposed, which takes into account both the pumping energy of the system and the energy produced, by translating the productivity of biomass to energy, through some expressions proposed in this thesis, this expression combined with the model previously proposed is able to reach optimal regions for the PBR operation in accurate way. Finally, it was found that the economic impact of the use of economic control was positive for the system, due to the fact that its objective function and prediction model take into account not only the productivity of the system, but also the energy costs associated with pumping and mixing.